EVALUASI RANTAI SUPLAI WISATA DALAM PERENCANAAN PEMBANGUNAN EKOWISATA DI KAWASAN WISATA CIBODAS, JAWA BARAT - Tutut Sunarminto; Dudung Darusman; Hadi S Alikodra; Ricky Avenzora (Department of Forest Resources Conservation and Ecotourism - IPB University, 2014)
In order to get a better quality from supply of ecotourism activities in Cibodas Ecotourism Destination Area, a research about supply chain has been done. A set of closed-ended questionaire has been distributed to collect visitor opinion and perspective on supply condition in the area; by using a score system of Likert.The result showed at least 6 important parties in the supply chain in the area, i.e: (1) Government as regulator, (2) Government as destination site owner and management, (3) Non Governmental Business Unit Institution, (4) Major Private Sectors, (5) Midle Private Sectors and (6) Small Private Sectors. Actually, the important element of a supply chain had been going, but however almost all of them haven’t been in their best productivity performance yet. Because of the classic problem of low-capacity of human resources is still going, the in-situ quality of ecotourism experiences and satisfaction also became a problem for the visitors. Theoritically, the quality of ecotourism resources in the area had high-quality values, but however no single ecotourist characteristic group that keen to score the ecotourism supply in the area for the maximum score. Most of supply variables are only scored by the visitor on “fair” value. In order to solve those problems in supply-chain, a concept called “booked-access destinantion” is proposed. The booked access destinantion is believe that not only pattornize the tourist behaviour but also will give the stake holder of supply chain a chance to get better potential price. Keywords: Supply Chain, Ecotourism, Cibodas, Likert scale, West Java